Effects of condensed tannins from Leucaena leucocephala (LAM.) de wit hybrid on methane mitigation, rumen fermentation, and populations of methanogens and protozoa in vitro - Tan, Hui Yin (2012)
Methane is the second most important greenhouse gas that contributes to global warming and climate change. Methane production from livestock, predominantly ruminants, accounts to about one-third of global anthropogenic methane production. Methane produced during ruminal fermentation also represents a loss of gross energy consumed up to 12%. Thus, there is an urgent need to reduce methane emission from ruminants. This study was carried out to investigate the effects of condensed tannins (CTs), a plant secondary metabolite, from Leucaena leucocephala hybrid-Rendang (LLR) on methane mitigation, rumen fermentation, and molecular diversities and populations of methanogens and protozoa in vitro. The study was divided into four experiments. In the first experiment, extraction, purification and determination of molecular weights of crude and pure CT extracts from LLR were carried out. It was found that the number-average molecular weights (Mn) determined using quadrupole time-offlight mass spectrometer were 1087.99 and 1070.51 Da for crude and pure CT extracts, respectively. In the second experiment, different levels of crude and pure CTs extracted from LLR were investigated for their effects on methane production and rumen fermentation parameters such as pH, dry matter degradability, nitrogen disappearance and volatile fatty acid concentrations. Crude CT concentrations of 0 (control), 10, 25, 40 and 55 mg, and 500 mg of oven dried guinea grass (Panicum maximum) with 40 ml of buffered rumen fluid were incubated for 24 h using an in vitro gas production procedure. Results showed that total gas production decreased linearly (P<0.05) with increasing inclusions of crude CT levels. A linear decrease (P<0.01) in methane production was observed at higher concentrations of crude CTs of 40 and 55 mg/500 mg DM, with reduction of 32.4% for both levels when compared to the control. Total volatile fatty acid concentration (mmol/L) decreased linearly (P<0.01) and propionate production increased at a linear rate (P<0.01) with additions of crude CTs. However, at 40 and 55 mg of crude CTs, in vitro dry matter (DM) degradation was significantly (P<0.05) reduced. Pure CT concentrations of 0 (control), 10, 15, 20, 25 and 30 mg were also studied using the in vitro gas production procedure. Results showed that total gas (ml/g DM) decreased (linear P<0.01; quadratic P<0.05) with increased levels of pure CT inclusion. Methane production (ml/g DM) decreased (linear P<0.01; quadratic P<0.01) with increasing levels of pure CTs. Total volatile fatty acid concentration (mmol/L) decreased linearly (P<0.01) and quadratically (P<0.01) with increasing pure CT inclusions. In vitro DM degradation and nitrogen disappearance declined linearly (P<0.01) with increasing levels of pure CTs. The results of the study showed that pure CTs from LLR at a relatively low level of 20 mg could reduce methane production by 57% without negatively affecting in vitro DM degradability and in vitro nitrogen disappearance. Although crude CTs and pure CTs at higher concentrations could also reduce methane emissions, they have substantive negative effects on DM digestibility. Experiments three and four were carried out to estimate the populations and molecular diversities of methanogenic archaea and protozoa. Estimation of rumen methanogens and protozoal populations using microbiological methods and real-time PCR assay showed linear reductions in total methanogens (P<0.01) and total protozoa (P<0.01) with increasing levels of CTs. CT inclusion exhibited linear, quadratic and cubic effects on methanogens in the order Methanobacteriales. Molecular diversities of rumen methanogens and protozoa from bovine rumen fluid incubated with pure CTs at 20 mg/500 mg DM or without CTs (control) was investigated using 16S rRNA and 18S rRNA gene libraries, respectively. The predominant order of rumen methanogens in the 16S rRNA gene libraries of the control and CT treatment was found to belong to a novel group of rumen archaea that is distantly related to the order Thermoplasmatales, with 59.5% (15 phylotypes) and 81.4% (21 phylotypes) of the total clones from the control and treatment clone libraries, respectively. The 16S rRNA gene library of the control was found to have higher proportions of methanogens in the orders Methanomicrobiales (32%) and Methanobacteriales (8.5%) as compared to those of the CT treatment clone library (16.9% and 1.7% respectively). The phylotype placed in the order Methanosarcinales was only found in the control clone library. The study indicated that CTs could alter the diversity of bovine rumen methanogens. The 18S rRNA gene libraries of the protozoa revealed that all the clones were distributed in the orders Entodiniomorphida and Trichostomatida. A higher percentage of clones in the genus Entodinium (11.1% increase), and a lower percentage of clones in the genera Ostracodinium and Anoplodinium (5% and 3% decrease, respectively) were found in the CT treatment clone library. In conclusion, the results indicated that pure CTs at the concentration of 20 mg/500 mg DM has the potential to be used as a feed supplement to reduce methane production by decreasing and altering the total methanogenic archaea and protozoal populations in ruminants, without adversely affecting DM degradability and nitrogen disappearance. However, in vivo experiments should be carried out to further evaluate the efficacy of CTs in methane mitigation.